The Influence of Place, Price, and Product Quality on Purchase Decisions at Padang Murah Restaurant in Ponorogo - Hayatul Maemunah; Muhammad Ilyas (Jurnal Manajemen dan Bisnis Indonesia, 2026)
This study examines the effects of place, price, and product quality on consumer purchase decisions at Padang Murah Restaurant in Ponorogo amid growing competition in the local culinary MSME sector. Grounded in marketing mix theory and Islamic consumer behavior principles, this study employs a quantitative survey approach. Data were collected through questionnaires from 375 consumers selected using purposive sampling. Data analysis was conducted using multiple linear regression with SPSS version 27, including validity, reliability, classical assumption, t-test, F-test, and coefficient of determination analyses. The results show that place, price, and product quality have positive and significant effects on purchase decisions, both partially and simultaneously. The coefficient of determination (R²) of 0.753 indicates that these three variables explain 75.3% of the variation in purchase decisions, while the remaining 24.7% is explained by other factors outside the model. These findings highlight the importance of strategic location, fair and affordable prices, and consistent product quality in influencing consumer purchasing behavior.